A 0.19 ppm/°C bandgap reference circuit with high-PSRR *Project supported by the National Natural Science Foundation of China (Nos. BK20150627, 61674030), the Natural Science Foundation of Jiangsu Province (No. 61504025), and the National Key research and Development Plan (No. 2017YFB0402900). (September 2018) - Leng, Jing; Lu, Yangyang; Zhang, Yunwu; Xu, Huan; Hu, Kongsheng; Yu, Zhicheng; Sun, Weifeng; Zhu, Jing
Abstract: A high-order curvature-compensated CMOS bandgap reference (BGR) topology with a low temperature coefficient (TC) over a wide temperature range and a high power supply reject ratio (PSRR) is presented. High-order correction is realized by incorporating a nonlinear current I NL, which is generated by ∆ V GS across resistor into current generated by a conventional first-order current-mode BGR circuit. In order to achieve a high PSRR over a broad frequency range, a voltage pre-regulating technique is applied. The circuit was implemented in CSMC 0.5 μ m 600 V BCD process. The experimental results indicate that the proposed topology achieves TC of 0.19 ppm/°C over the temperature range of 165 °C (−40 to 125 °C), PSRR of −123 dB @ DC and −56 dB @ 100 kHz. In addition, it achieves a line regulation performance of 0.017%/V in the supply range of 2.8–20 V.